Distinct patterns of prion strain deposition and toxicity in a novel whole brain organotypic slice culture system - Hailey Pineau; Valerie L. Sim (Scientific Reports)
Abstract Prion diseases are fatal transmissible neurodegenerative diseases that affect many mammals, including humans, caused by the templated misfolding of the prion protein. Different conformations of misfolded prions can occur, leading to distinct disease phenotypes or strains and the accumulation of prions in distinct brain regions. How prion structure influences this brain tropism is not clear, but the transmissible nature of prion diseases has allowed for the development of ex vivo brain slice models of disease. To date, work has been done in cerebellar cultures, but prion diseases are known to differentially affect many other brain regions. We have adapted this approach to a coronally sliced whole brain organotypic culture and demonstrate distinct profiles of cytotoxicity and neuronal loss upon exposure to four mouse-adapted scrapie strains. We were able to induce infection both diffusely through submersion of slice cultures in infectious media and locally through contact with prion-coated stainless-steel wires. Moreover, we observed consistent strain-specific regional differences in prion deposition by 8 weeks of infection, recapitulating what is seen in vivo. We predict that coronal whole brain organotypic slice cultures can be a powerful tool for elucidating strain-specific mechanisms of prion spread and pathology.